Bahasa figuratif dalam puisi-puisi karya Chairil Anwar - Asna Ntelu; Ellyana Hinta; Yelin Yasin; Supriyadi Supriyadi (Universitas Lampung, 2020)
Figurative language in poetry is important to study because figurative language is one part of the physical structure of poetry that can animate or cause certain effect and cause certain connotation of words contained in poetry. This research was carried out to obtain figurative language description in Chairil Anwar's poems. The procedure that was passed from data collection to data interpretation were (a) identifying figurative languages in Chairil Anwar's poems, (b) understanding languages in figurative form, (c) understanding the description of meaning contained in it, and ( d) marking the units of segmentation in the form of figurative language. Data analysis was based on three processes, namely the reduction process, the data presentation process, and the verification process. Based on the result of the study obtained, the figurative language is closely related to reality life, poets have a specific purpose in using figurative language, reader must try to understand figurative language in an effort to intact the meaning of a poem, in the poems of Chairil Anwar a number of the beauty of figurative language that can help the reader interpret the meaning of the lines contained there in. Figurative language is presented in his poems to make it easier for reader to interpret the poem. In his poems, Chairil Anwar does not just mention figurative language so that the poems seem interesting, but the inclusion of figurative language was done carefully so that the reader is able to know the meaning of figurative language even though it is considered difficult to interpret.http://dx.doi.org/10.23960/aksara/v21i1.pp41-56